2021
DOI: 10.1088/1755-1315/828/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seaweed Extract (Sargassum sp.) on Growth and Yield Enhancement of Mustard Greens (Brassica juncea L.)

Abstract: This research aims to study the effect of applying various seaweed extract concentrations on mustard greens growth and yield (Brassica juncea L.). The study was conducted at the Faculty of Agriculture Screen House, University Tadulako Palu, and arranged using a randomized block design (RBD) with six treatments. These were, without seaweed extract (E0), as well as 20% (E1), 40% (E2), 60% (E3), 80% (E4), and 100% (E5) seaweed extract concentration. The experiment was repeated four times, thus, there were 24 expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The mechanism as to how seaweed extracts and shrimp wastes improve the growth and vigour of plants has been difficult to elucidate as they contain numerous bioactive compounds which is not fully researched. In a study comparing different concentrations of seaweed extracts, Yusuf et al (2021) reported that seaweed extract application affects the number of leaves in mustard plants at 14, 21, and 28 days after planting (DAP). The highest number of leaves (5.75 pieces) was produced by the 20% seaweed concentration treatment.…”
Section: Figmentioning
confidence: 99%
“…The mechanism as to how seaweed extracts and shrimp wastes improve the growth and vigour of plants has been difficult to elucidate as they contain numerous bioactive compounds which is not fully researched. In a study comparing different concentrations of seaweed extracts, Yusuf et al (2021) reported that seaweed extract application affects the number of leaves in mustard plants at 14, 21, and 28 days after planting (DAP). The highest number of leaves (5.75 pieces) was produced by the 20% seaweed concentration treatment.…”
Section: Figmentioning
confidence: 99%